Effects of Storytelling Instruction on the Speaking Skills of Grade V Students - Cunandar, Dadang; Muhamad Indanus (LPPM Universitas Advent Indonesia, 2025)
This study examines the effect of implementing the storytelling method on the speaking skills of fifth-grade elementary school students. A pre-experimental one-group pretest–posttest design was employed. The population and sample consisted of 25 Grade V students of SD Negeri 2 Bakom, Darma District, Kuningan Regency, selected using saturated sampling. Data were collected through observation, speaking performance tests, and documentation. Instruments included teacher and student observation sheets and speaking skill tests. Data analysis involved descriptive statistics, normality and homogeneity tests, and hypothesis testing using a paired t-test at a 0.05 significance level. Results showed that teacher activity obtained a total score of 54 with a mean of 3.7 (good category). Student activity reached a total score of 34 with a mean of 3.09 or 77.2% (good category). The pretest mean score was 46 (low), while the posttest mean score increased to 76 (high). Hypothesis testing indicated that tcount > ttable (2.24 > 2.012), leading to the rejection of the null hypothesis. It is concluded that the storytelling method has a significant positive effect on improving students’ speaking skills in Indonesian language learning at the elementary level.